2011
DOI: 10.1186/alzrt67
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor and granulocyte colony-stimulating factor reduce β-amyloid deposits in the brains of APP/PS1 transgenic mice

Abstract: IntroductionAlzheimer's disease (AD) is widely recognized as a serious public health problem and heavy financial burden. Currently, there is no treatment that can delay or stop the progressive brain damage in AD. Recently, we demonstrated that stem cell factor (SCF) in combination with granulocyte colony-stimulating factor (G-CSF) (SCF+G-CSF) has therapeutic effects on chronic stroke. The purpose of the present study is to determine whether SCF+G-CSF can reduce the burden of β-amyloid deposits in a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Bone marrow-derived microglia are not increased by SCF + G-CSF in the conditions of CADASIL (present study) and chronic stroke (Piao et al, 2009), but SCF + G-CSF increases the bone marrow-derived microglia in the brains of mice carrying Alzheimer's disease genes (Li et al, 2011). In the chronic stroke brain, bone marrow-derived endothelia are increased by SCF + G-CSF treatment, while this type of cell appears to be decreased by SCF + G-CSF in CADASIL brain (present study).…”
Section: Recruitment Of Bone Marrow-derived Cells In the Brains Of Camentioning
confidence: 73%
“…Bone marrow-derived microglia are not increased by SCF + G-CSF in the conditions of CADASIL (present study) and chronic stroke (Piao et al, 2009), but SCF + G-CSF increases the bone marrow-derived microglia in the brains of mice carrying Alzheimer's disease genes (Li et al, 2011). In the chronic stroke brain, bone marrow-derived endothelia are increased by SCF + G-CSF treatment, while this type of cell appears to be decreased by SCF + G-CSF in CADASIL brain (present study).…”
Section: Recruitment Of Bone Marrow-derived Cells In the Brains Of Camentioning
confidence: 73%
“…It has been noted to mediate chemoattractant activity for neural stem/progenitor cell migration and thought to play a repair role in models of stroke . In the context of AD it has been reported to be low in the CSF and plasma of AD patients and therapeutic effects of systemic SCF administration in mice models have shown promise in reducing amyloid …”
Section: Discussionmentioning
confidence: 99%
“…Thanks to those receptors astrocytes are not only capable to respond to the classical neurotransmitters glutamate and γ-aminobutyric acid (GABA) released from synapses [through metabotropic glutamate receptors (mGluRs) mGluR1-5 and GABA B receptors respectively; Pasti et al, 1997; Kang et al, 1998] but also to neuromodulators like acetylcholine (Takata et al, 2011; Navarrete et al, 2012) and dopamine (Khan et al, 2001). Moreover, purines like adenosine-5′-triphosphate (ATP) and adenosine (co-)released from synapses or other astrocytes can be sensed by astrocytes (Jourdain et al, 2007; Santello et al, 2011) and play a role in the propagation/amplification of Ca 2+ signals through the astrocytic syncytium (Poskanzer and Yuste, 2011) or serve as a signal for microglial reaction (Haynes et al, 2006). In addition to sensing axonal release of transmitters, astrocytes have been shown to respond to so-called retrograde signals: transmitters of postsynaptic or dendritic origin (Bernardinelli et al, 2011).…”
Section: How Are Astrocytes Activated?mentioning
confidence: 99%
“…Interfering with astrocyte signaling reduces the power of slow oscillations in vivo (Fellin et al, 2009), presumably through modulation of NMDARs and adenosine A1 receptors. Furthermore, in vitro experiments have shown that astrocytes control the frequency of cortical up-states (Poskanzer and Yuste, 2011). …”
Section: Astrocyte Modulation Of Network Excitabilitymentioning
confidence: 99%